Traditional Chinese Medicine formula Dai-Zong-Fang alleviating hepatic steatosis in db/db mice via gut microbiota modulation - Zhang, Li-Wei; Zhu, Li-Li; Zhu, Xiao-Yun; Fu, Shou-Qiang; Liu, Xi-Ming (Frontiers in Pharmacology, 2024)
Introduction: Hepatic steatosis is a hepatic pathological change closely associated with metabolic disorders, commonly observed in various metabolic diseases such as metabolic syndrome (MetS), with a high global prevalence. Dai-Zong-Fang (DZF), a traditional Chinese herbal formula, is widely used in clinical treatment for MetS, exhibiting multifaceted effects in reducing obesity and regulating blood glucose and lipids. This study aims to explore the mechanism by which DZF modulates the gut microbiota and reduces hepatic steatosis based on the gut-liver axis. Methods: This study utilized db/db mice as a disease model for drug intervention. Body weight and fasting blood glucose were monitored. Serum lipid and transaminase levels were measured. Insulin tolerance test was conducted to assess insulin sensitivity. Hematoxylin and eosin (HE) staining was employed to observe morphological changes in the liver and intestine. The degree of hepatic steatosis was evaluated through Oil Red O staining and hepatic lipid determination. Changes in gut microbiota were assessed using 16S rRNA gene sequencing. Serum lipopolysaccharide (LPS) levels were measured by ELISA. The expression levels of intestinal tight junction proteins, intestinal lipid absorption-related proteins, and key proteins in hepatic lipid metabolism were examined through Western blot and RT-qPCR. Results: After DZF intervention, there was a decrease in body weight, alleviation of glucose and lipid metabolism disorders, reduction in serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels, and mitigation of insulin resistance in mice. DZF significantly modulated the diversity of the gut microbiota, with a notable increase in the abundance of the Bacteroidetes phylum. PICRUSt indicated that DZF influenced various functions in gut microbiota, including carbohydrate and amino acid metabolism. Following DZF intervention, serum LPS levels decreased, intestinal pathological damage was reduced, and the expression of intestinal tight junction protein occludin was increased, while the expression of intestinal lipid absorption-related proteins cluster of differentiation 36 (CD36) and apolipoprotein B48 (ApoB48) were decreased. In the liver, DZF intervention resulted in a reduction in hepatic steatosis and lipid droplets, accompanied by a decrease fatty acid synthase (FASN) and stearoyl-CoA desaturase 1 (SCD1) and fatty acid transport protein 2 (FATP2). Conversely, there was an increase in the expression of the fatty acid oxidation-related enzyme carnitine palmitoyltransferase-1𝛂 (CPT-1𝛂). Conclusion: DZF can regulate the structure and function of the intestinal microbiota in db/db mice. This ameliorates intestinal barrier damage and the detrimental effects of endotoxemia on hepatic metabolism. DZF not only inhibits intestinal lipid absorption but also improves hepatic lipid metabolism from various aspects, including de novo lipogenesis, fatty acid uptake, and fatty acid oxidation. This suggests that DZF may act on the liver and intestine as target organs, exerting its effects by improving the intestinal microbiota and related barrier and lipid absorption functions, ultimately ameliorating hepatic steatosis and enhancing overall glucose and lipid metabolism.